The influence of module-based coronary heart disease risk factor education on the level of patient knowledge at Hospital of PKU Muhammadiyah Yogyakarta - Muzaenah, Tina; Sriyati, Sriyati (Indonesian Nursing Journal, 2024)
Background: Coronary heart disease (CHD) is a leading cause of morbidity and mortality worldwide. Effective patient education regarding CHD and its risk factors is essential for prevention and management. Purpose: This study aims to evaluate the effectiveness of a module-based educational intervention on improving patient knowledge of CHD risk factors. Methods: This quasi-experimental study employed a pre-test and post-test control group design. A total of 34 participants were selected via quota sampling, with 17 assigned to the intervention group and 17 to the control group. Participants' knowledge levels were measured using the Heart Disease Facts Questionnaire (HDFQ) before and after receiving education on CHD risk factors through a structured booklet and Counselling Events Units (SAP). Results: Statistical analysis using the Mann-Whitney test revealed a significant increase in the knowledge levels of the intervention group compared to the control group (p = 0.001), indicating the effectiveness of the module-based education. Conclusion: Module-based education on CHD risk factors significantly improves patient knowledge. This approach can be an effective educational tool in clinical settings for enhancing patient understanding and reducing CHD risk.